Allium sultanae-ismailii (Amaryllidaceae), a new species from eastern Turkey - Yildirim, Hasan (Phytotaxa, 2019)
Allium sultanae-ismailii Yıldırım (Amaryllidaceae) is described here as a new species. Diagnostic morphological characters, a full description, and detailed illustrations are given herein. A. sultanae-ismailii is restricted to Mt. Akbabaçalı in Darende district of Malatya province in eastern Anatolia, Turkey. According to its morphological features, it belongs to Allium subgen. Melanocrommyum sect. Melanocrommyum. It shows morphological similarities with A. purpureoviride, which belong to the same subgenus and section. However, it is easily distinguished from this latter species by the dark purple tepals, shorter stem, initially stellate perianth segments, longer style, undivided and very short tripartite stigma, and distribution at higher altitudes.